2017
DOI: 10.3390/diseases5010012
|View full text |Cite
|
Sign up to set email alerts
|

Milk’s Role as an Epigenetic Regulator in Health and Disease

Abstract: Abstract:It is the intention of this review to characterize milk's role as an epigenetic regulator in health and disease. Based on translational research, we identify milk as a major epigenetic modulator of gene expression of the milk recipient. Milk is presented as an epigenetic "doping system" of mammalian development. Milk exosome-derived micro-ribonucleic acids (miRNAs) that target DNA methyltransferases are implicated to play the key role in the upregulation of developmental genes such as FTO, INS, and IG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 406 publications
(638 reference statements)
1
109
0
3
Order By: Relevance
“…First, only four cohort studies included in our meta-analysis, which limited the further subgroup analysis by study design. [44][45][46] Intriguingly, it was reported that the mortalityand bone fracture-increasing effects of milk intake had only been detected in relation to intake of pasteurized milk but not to fermented dairy products such as yogurts or cheeses. Second, our study was also limited by the self-reported diagnosis of acne as well as the ambiguous diagnostic criteria for acne in several included studies, both of which could result in a potential mis-validation of acne status and a recall and selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…First, only four cohort studies included in our meta-analysis, which limited the further subgroup analysis by study design. [44][45][46] Intriguingly, it was reported that the mortalityand bone fracture-increasing effects of milk intake had only been detected in relation to intake of pasteurized milk but not to fermented dairy products such as yogurts or cheeses. Second, our study was also limited by the self-reported diagnosis of acne as well as the ambiguous diagnostic criteria for acne in several included studies, both of which could result in a potential mis-validation of acne status and a recall and selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA hsa‐miR‐148a‐3p is consistently the most abundant microRNA in breast milk, most likely because of its importance for lactation and its enrichment in mammary gland cells (Chen et al., ; Do, Dudemaine, Li, & Ibeagha‐Awemu, ; Gu et al., ; Muroya et al., ). It is then with little surprise that this microRNA is the most studied milk microRNA (Benmoussa et al., ; Golan‐Gerstl et al., ; Melnik, ; Melnik & Schmitz, , ; Simpson et al., ; van Herwijnen et al., ). Other less‐expressed microRNAs have nevertheless been investigated in breast milk, like the immunity‐related microRNAs hsa‐miR‐223 or hsa‐miR‐146a (Iannaccone et al., ; Liao et al., ; Perri et al., ; van Herwijnen et al., ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
“…Notably, development‐associated miR‐142a‐5p, miR‐223‐5p, miR‐10b‐5p, miR‐142a‐3p, and miR‐466d‐3p were differentially impacted by HFD (Chen et al., ). Therefore, dietary patterns in the mothers might impact the microRNA profile, possibly allowing for diagnosis of dietary deviation (for example, malnutrition) or, in the case of microRNA transfer to the infant (Melnik & Schmitz, , ; Zempleni et al., ), altering the potential outcome of milk microRNAs bioactivity.…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Greater efforts are needed to improve our health by reducing calories and growth promoting foods, like milk [28] and animal protein [21]. In addition, a population of 10 billion people places our environment and survival under serious threat.…”
Section: Resultsmentioning
confidence: 99%